2017
DOI: 10.1016/j.neuron.2017.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Input-Specific Plasticity and Homeostasis at the Drosophila Larval Neuromuscular Junction

Abstract: Summary Synaptic connections undergo activity-dependent plasticity during development and learning, as well as homeostatic re-adjustment to ensure stability. Little is known about the relationship between these processes, particularly in vivo. We addressed this with novel quantal resolution imaging of transmission during locomotive behavior at glutamatergic synapses of the Drosophila larval neuromuscular junction. We find that two motor input types – Ib and Is – provide distinct forms of excitatory drive durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
244
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(271 citation statements)
references
References 68 publications
21
244
2
Order By: Relevance
“…In particular, postsynaptic overexpression of a constitutively active form of CamKII blocks PHP expression in GluRIIA mutants. More recently, a local reduction in phosphorylated (active) CamKII (pCamKII) in the postsynaptic compartment was observed in GluRIIA mutants (Newman et al, 2017). However, pCamKII levels have never been examined in the context of PhTx or Tor-OE forms of PHP signaling.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, postsynaptic overexpression of a constitutively active form of CamKII blocks PHP expression in GluRIIA mutants. More recently, a local reduction in phosphorylated (active) CamKII (pCamKII) in the postsynaptic compartment was observed in GluRIIA mutants (Newman et al, 2017). However, pCamKII levels have never been examined in the context of PhTx or Tor-OE forms of PHP signaling.…”
Section: Resultsmentioning
confidence: 99%
“…However, we found that neither mEPSP amplitude nor frequency is significantly changed when calcium is absent or calcium concentrations are elevated in the extracellular saline (Figure S1). Next, we imaged postsynaptic calcium influx using a genetically encoded calcium indictor (SynapGCaMP6f) targeted to postsynaptic glutamate receptors at the Drosophila NMJ (Newman et al, 2017). This reporter is capable of detecting calcium transients during individual mEPSP events (Newman et al, 2017), but the response during mEPSP events across varying ranges of extracellular calcium has not been determined.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations